Optical trapping of metallic Rayleigh particle by combined beam - 程科 钟先琼 向安平 (Optoelectronics letters, 2012)
Radiation forces and trapping stability of metallic （i.e. gold） Rayleigh particle by combined beam are analyzed, and the combined beam is formed by superimposing two partially coherent off-axis fiat-topped beams. The dependences of radiation forces on off-axis distance parameter, correlation length and particle radius are illustrated by numerical examples. The results show that there exist critical values d0,c and or σ0,c for the combined beam. For 0〈d ≤ d0,c or 0〈σ0 ≤ σ0,c the Gaussianlike intensity profile takes place at the geometrical focal plane, so that the transverse gradient force can act as restoring force. As the off-axis distance parameter increases or the correlation length decreases, the maximal intensity, the radiation force and trapping stiffness become smaller, while the transverse and longitudinal trapping ranges become larger. In comparison with a single beam, the combined beam is more favourable for trapping metallic Rayleigh particle owing to the stronger trapping stiffness and the larger trapping range.